Let's solve your equation step-by-step. ( 2 x − 3 )( x + 10 )= 70

Step 1: Simplify both sides of the equation. 2 x 2 + 17 x − 30 = 70

Step 2: Subtract 70 from both sides. 2 x 2 + 17 x − 30 − 70 = 70 − 70 2 x 2 + 17 x − 100 = 0

Step 3: Factor left side of equation. ( 2 x + 25 )( x − 4 )= 0

Step 4: Set factors equal to 0. 2 x + 25 = 0 or x − 4 = 0 x = -4

(length ) , x= -25/ 4 (width ) -4+10 = 6 (length works)

2(-25/ 4)-3 = -11 its negative and that is not possible so we take out the root for width